2023
DOI: 10.1177/00219983231191585
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic buckling response of variable fiber spacing composite plate under thermal environment

Prateek Chandrakar,
Narayan Sharma,
Dipak Kumar Maiti

Abstract: The effectiveness of variable fiber spacing composite (VFSC) laminates subjected to thermal loading is compared with uniformly distributed fiber composite (UDFC) laminates. The higher-order shear deformation theory (HSDT) is adopted to develop a FE model for estimating critical thermal buckling load. Three types of fiber distribution patterns are considered to study the effect of the non-uniform spacing distribution of fiber on thermal buckling, and the results are compared with UDFC. Further, a surrogate mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Properties of metallic materials, widely used in the aeronautical industry, are already known. However, the structural properties of composite materials and their effect on structural properties [6,7,8,9], structural modes and aeroelastic response [6,7,8,10] are also a current topic of research. Some research has shown the use of piezoelectric materials to control the aeroelastic response of structures built with composite material [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Properties of metallic materials, widely used in the aeronautical industry, are already known. However, the structural properties of composite materials and their effect on structural properties [6,7,8,9], structural modes and aeroelastic response [6,7,8,10] are also a current topic of research. Some research has shown the use of piezoelectric materials to control the aeroelastic response of structures built with composite material [11,12].…”
Section: Introductionmentioning
confidence: 99%